Self-regulated learning processes across different physiotherapy clinical procedural skills and time intervals: A SRL microanalysis study - Cecilio-Fernandes, Dario; Medina-Ramírez, Raquel; Sandars, John; Costa, Manuel João (Medical teacher, 2023)
The performance of a clinical procedural skill by an individual student is associated with their use of Self-Regulated Learning (SRL) processes. However, previous research has not identified if an individual student has a similarity in their use of SRL processes across different clinical procedural skill tasks and at a time interval. The aim of this pilot study was to explore the similarity in the use of SRL processes by individual students across different clinical procedural skill tasks and at a time interval. SRL-microanalysis was used to collect within-subject data on undergraduate physiotherapy students' use of the two key SRL processes (planning and monitoring) during their performance of different goniometry clinical procedural skills tasks and also at a fourth month interval. An individual student's use of key SRL processes across different clinical procedural skill tasks and at a time interval was similar. Also, this similarity was identified for students with initial successful and unsuccessful performances. Our findings have implications for the future wider practical implementation of SRL microanalysis to inform personalised SRL feedback for developing the clinical procedural skills of individual students. Further research with a greater number of students and across a wider range of clinical procedural skills will be required to confirm our findings, and also its effectiveness on feedback and future performance.